2016
DOI: 10.3390/ijerph13100997
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Mineralization of Benzohydroxamic Acid by Synthesized Mesoporous La/TiO2

Abstract: Rare earth element La-doped TiO2 (La/TiO2) was synthesized by the sol-gel method. Benzohydroxamic acid was used as the objective pollutant to investigate the photocatalytic activity of La/TiO2. The physicochemical properties of the prepared materials were characterized by X-ray diffraction, X-ray photoelectron spectroscopy, UV-vis diffuse reflectance spectroscopy, specific surface area and porosity, scanning electron microscopy and transmission electron microscopy. As a result, the doping of La could inhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…RE/TiO 2 were prepared by the sol-gel method according to previous research [10]. Rare-earth nitrate in the required stoichiometry was mixed with 2 mL deionized water, 2 mL acetic acid and 10 mL absolute ethanol, and the mixture solution after stirring was noted as solution A.…”
Section: Preparation Of Re/tiomentioning
confidence: 99%
See 1 more Smart Citation
“…RE/TiO 2 were prepared by the sol-gel method according to previous research [10]. Rare-earth nitrate in the required stoichiometry was mixed with 2 mL deionized water, 2 mL acetic acid and 10 mL absolute ethanol, and the mixture solution after stirring was noted as solution A.…”
Section: Preparation Of Re/tiomentioning
confidence: 99%
“…For example, there needs to be 5 or more days to get to the removal efficiency of 85% for benzohydroxamic acid (BHA, the most widely-used collector in the flotation industry at present) with the method of biodegradation [9]. However, our previous studies indicated that La/TiO 2 and Yb/TiO 2 possessed high photodegradation activity to BHA (the removal efficiency was up to 90% in 2 h) [10]. TiO 2 has been considered as the most promising photocatalyst among various semiconductor photocatalyst materials due to its benign physicochemical property and low cost [11].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Parida reported that La‐doped or Ce‐doped TiO 2 can inhibit the anatase to rutile phase transformation and extend light‐absorption to the visible region, thus greatly improving the photocatalytic performance of TiO 2 . In addition, studies showed that doping with rare earth elements such as La, Ce, Gd, and Sm can inhibit electron‐hole recombination, thus improving the photocatalytic efficiency . Xu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Pure TiO 2 and Yb/TiO 2 catalysts were synthesized by sol-gel method [ 13 , 14 , 15 ]. The detailed prepared processes are as follows.…”
Section: Methodsmentioning
confidence: 99%
“…However, five or more days were needed to obtain a removal efficiency of 85% under the conditions of additional nutrition. Our previous study indicated that La/TiO 2 possessed high activity with respect to BHA [ 13 ]. However, the products of BHA and the oxidation mechanisms were not discussed in the previous study.…”
Section: Introductionmentioning
confidence: 99%